The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4314/ejhs.v31i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Primary Hospitals in Providing Neonatal Intensive Care Services in Ethiopia

Abstract: BACKGROUND፡ The Ethiopian neonatal mortality has not shown much progress over the years. In light of this, the country has introduced interventions such as the utilization of newborn corners and neonatal intensive care units to avert preventable neonatal deaths. This study was conducted to assess readiness of primary hospitals in providing neonatal intensive care services.METHODS: A health facility based cross-sectional study design was employed where data were collected using both prospective and retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Likewise, the level of care at the health post, health center or hospital level was substandard. The overall structural standards for a NICU were met by 63% of the studied primary hospitals (32), and 65.2% of the required equipment, and 72.2% of medicines, were met in the NICU ward of a referral hospital (51). Similarly, Biadgo, et al (19) reported that only 15.6% of the studied health facilities ful lled the standards for quality childcare provision.…”
Section: Structurementioning
confidence: 83%
See 1 more Smart Citation
“…Likewise, the level of care at the health post, health center or hospital level was substandard. The overall structural standards for a NICU were met by 63% of the studied primary hospitals (32), and 65.2% of the required equipment, and 72.2% of medicines, were met in the NICU ward of a referral hospital (51). Similarly, Biadgo, et al (19) reported that only 15.6% of the studied health facilities ful lled the standards for quality childcare provision.…”
Section: Structurementioning
confidence: 83%
“…In addition, seven (26.9%) studies assessed health outcomes at both individual and population levels. Five of the studies (71.4%) looked at the effectiveness of interventions in reducing childhood mortality at a population level(32,41,45, 62, 63), while four (57.1%) examined clinical or treatment outcomes, including recovery and complication rates and adverse effects of clinical treatment(32, 37,…”
mentioning
confidence: 99%
“…The average number of neonatal intensive care unit-trained nurses per primary hospital was below the recommended national standard. The survey also found that the minimum national requirement for medical equipment and renewables for neonate care was met only by 24% hospitals, 65% for essential laboratory tests, and 87% for clinical services and procedures [13].…”
Section: Discussionmentioning
confidence: 99%
“…The minimum national requirement for medical equipment and renewables was ful lled by 24% of hospitals, 65% for essential laboratory tests, and 87% for clinical services and procedures. (10).…”
Section: Introductionmentioning
confidence: 99%